BIOACTIVE DITERPENES AND SESQUITERPENES FROM THE RHIZOMES OF WILD GINGER (SIPHONOCHILUS AETHIOPICUS (SCHWEINF) B.L BURTT) - Igoli, Ngozichukwuka; Obanu, Zak; Gray, Alexander; Clements, Carol (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Wild ginger (Siphonochilus aethiopicus (Schweinf) B.L Burtt) is used in traditional medicines in the West and South of Africa. In the present study, some of the chemical components and the crude hexane extract of wild ginger were evaluated for their in vitro bioactivity. The components isolated from the plant for the first time are: epi-curzerenone, furanodienone, 8(17),12E-labdadiene-15,16-dial, 15-hydroxy-8(17),12E-labdadiene-16-al and 16-oxo-8(17),12E-labdadiene-15-oic acid. Cytotoxicity determinations for five cell lines: SH-SY5Y (human, Caucasian, bone marrow, neuroblastoma), Jurkat (human, peripheral blood, leukaemia T cell), L929 (mouse, CH3/connective tissue, areolar and adipose tumour cells), Hep G2 (human, Caucasian, hepatocellular carcinoma) and Hs 27 (normal, human, foreskin cells) were carried out. Anti-trypanosomal activity against Trypanosoma brucei brucei (S427) blood stream forms and anti-bacterial activity against Mycobacterium aurum (CIP .104482) were also investigated. The crude extract together with the labdane diterpenoids: 8(17),12E-labdadiene-15,16-dial and 15-hydroxy-8(17),12E-labdadiene-16-al showed specific cytotoxicity. They were not cytotoxic to cancerous human liver cells (Hep G2) at 100µg/ml. The sesquiterpenoids: epi-curzerenone and furanodienone showed no cytotoxicity at all. 8(17),12E-Labdadiene-15,16-dial showed significant anti-trypanosomal activity (MIC = 5.3 µM) just like the sesquiterpenoids (MIC = 6.9 µM) as compared to suramin activity (MIC = 10 µM). This anti-trypanosomal activity which is being reported for the first time indicates that the plant may be useful against sleeping sickness and nagana in cattle. The activity of 15-hydroxy-8(17),12E-labdadiene-16-al against M. aurum (MIC = 125µg/ml) was moderate. The labdane 8(17),12E-labdadiene-15,16-dial has the potential for an anti-cancer compound.